1) Show that the general expression for u, = guoJB, (n) becomes equivalent to the expression äy = u tanh %3D when J-1/2. %3D
1) Show that the general expression for u, = guoJB, (n) becomes equivalent to the expression äy = u tanh %3D when J-1/2. %3D
Related questions
Question

Transcribed Image Text:1) Show that the general expression for a, = guoJB, (n) becomes equivalent to the
expression y = u tanh
%3D
when J-1/2.
Expert Solution

This question has been solved!
Explore an expertly crafted, step-by-step solution for a thorough understanding of key concepts.
This is a popular solution!
Trending now
This is a popular solution!
Step by step
Solved in 4 steps with 4 images
